FAKTOR YANG BERHUBUNGAN DENGAN KEJADIAN ANEMIA PADA IBU HAMIL DI WILAYAH KERJA PUSKESMAS RASIMAH AHMAD KOTA BUKITTINGGI TAHUN 2024 - Mardiah, Ainal; Kasoema, Rahmi Sari; Amalina, Nurul; Nengsih, Widya; Delvina, Visti (Universitas Fort De Kock, 2024)
Anemia is a significant global health issue, with 4% of maternal deaths in developing countries still related to anemia during pregnancy. According to the World Health Organization (WHO) data from 2020, the prevalence of anemia among pregnant women remains high at 33%. In Indonesia, the prevalence of anemia among pregnant women ranges from 40% to 50%. This study aims to identify the factors associated with the incidence of anemia in pregnant women in the working area of Rasimah Ahmad Health Center, Bukittinggi City, in 2024. The research employed a descriptive analytic method with a cross-sectional approach and purposive sampling. Data analysis included both univariate and bivariate analyses. The study found no significant relationship between maternal age and the incidence of anemia in pregnant women, with a p-value of 0.072. However, there was a significant relationship between nutritional status and the incidence of anemia in pregnant women, with a p-value of 0.016. Additionally, there was a significant relationship between compliance with iron tablet consumption and the incidence of anemia, with a p-value of 0.021. Furthermore, there was a significant relationship between maternal knowledge about anemia and the incidence of anemia, with a p-value of 0.014. It can be concluded that there is a significant relationship between nutritional status, compliance in consuming fe tablets, and maternal knowledge regarding the incidence of anemia in pregnant women at the Rasimah Ahmad Community Health Center, Bukittinggi City in 2024. It is hoped that health workers at the community health center will be able to provide pregnant women with education about risk factors during pregnancy and how to deal with it so as to minimize the incidence of anemia by carrying out early detection to prevent anemia in pregnant women.